Legislation on Arithmetic Schools in Russia in the 1st Half of the 18th Century (with Reference to the Materials of the Complete Collection of Laws of the Russian Empire) - Alevtina Michaylovna Safronova; Olga Sergeyevna Kravchenko (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2015)
The authors of the article analyze the Edicts of the Russian tsars and Edicts of the Senate which regulated the principles of organization of a new form of primary educational institutions of Russia — arithmetic schools, established on the initiative of Peter I in 1714 and playing a significant role in the spread of the foundations of mathematical knowledge among the population. The authors reveal the reasons for the issuance of certain decrees, reveal their initiators, and trace the change of rules governing the principles of organization of schools, as well as make observations of the structure of the legislation in question.